A high-density consensus linkage map of white lupin highlights synteny with narrow-leafed lupin and provides markers tagging key agronomic traits. Issue 1 (December 2017) - Książkiewicz, Michał; Nazzicari, Nelson; Yang, Hua'an; Nelson, Matthew; Renshaw, Daniel; Rychel, Sandra; Ferrari, Barbara; Carelli, Maria; Tomaszewska, Magdalena; Stawiński, Stanisław; Naganowska, Barbara; Wolko, Bogdan; et al.
Abstract White lupin (Lupinus albus L.) is a valuable source of seed protein, carbohydrates and oil, but requires genetic improvement to attain its agronomic potential. This study aimed to (i) develop a new high-density consensus linkage map based on new, transcriptome-anchored markers; (ii) map four important agronomic traits, namely, vernalization requirement, seed alkaloid content, and resistance to anthracnose and Phomopsis stem blight; and, (iii) define regions of synteny between theL. albus and narrow-leafed lupin (L. angustifolius L.) genomes. Mapping of white lupin quantitative trait loci (QTLs) revealed polygenic control of vernalization responsiveness and anthracnose resistance, as well as a single locus regulating seed alkaloid content. We found high sequence collinearity between white and narrow-leafed lupin genomes. Interestingly, the white lupin QTLs did not correspond to previously mapped narrow-leafed lupin loci conferring vernalization independence, anthracnose resistance, low alkaloids and Phomopsis stem blight resistance, highlighting different genetic control of these traits. Our suite of allele-sequenced and PCR validated markers tagging these QTLs is immediately applicable for marker-assisted selection in white lupin breeding. The consensus map constitutes a platform for synteny-based gene cloning approaches and can support the forthcoming white lupin genome sequencing efforts.